Ultrasound-assisted deep eutectic solvent-based liquid–liquid microextraction for simultaneous determination of Ni (II) and Zn (II) in food samples. (1st November 2022) - Elahi, Fazal; Arain, Muhammad Balal; Ali Khan, Wajid; Ul Haq, Hameed; Khan, Asif; Jan, Faheem; Castro-Muñoz, Roberto; Boczkaj, Grzegorz
Graphical abstract: Highlights: Simultaneous extraction and determination of Ni (II) and Zn (II) in food samples. Minimization of solvents consumption. Selective extraction based on hydrophobic deep eutectic solvents. Highly sensitive method at ppb (µg/Kg) level. Universal sample preparation with easier and faster extraction procedure. Abstract: A new approach was developed for the simultaneous pre-concentration and determination of Ni (II) and Zn (II) in food samples. This method is based on ultrasound-assisted liquid–liquid micro extraction using hydrophobic deep eutectic solvent (DES) and 1, 10-phenanthroline as chelating agent. The effect of several parameters, such as pH, selection and volume of DES, amount of chelating agent, time of sonication and centrifugation, was studied. Under optimized conditions, the developed procedure offered exceptional sensitivity and linearity. The limit of detection was approximately 0.029 µg/Kg and 1.5 µg/Kg for Ni (II) and Zn (II), respectively. The proposed method was applied for the pre-concentration and determination of Ni (II) and Zn (II) in hydrogenated edible oils, fishes, and milk samples. The results of this study were compared with reported methods in the literature revealing its advantages.